Strategi Pemasaran Produk Low and High Involvement pada UMKM di Kota Meulaboh - Arizona, Bayu; Jalil, Ivon (Universitas Teuku Umar, 2024)
This research aims to analyze product marketing strategies with low and high levels of involvement in Micro, Small and Medium Enterprises in Meulaboh City. This research uses a descriptive qualitative method with a deep interview approach. The main focus of this research is to understand how in Meulaboh develop and implement marketing strategies based on six main indicators: (1) low emotional involvement, (2) level of brand awareness, (3) purchasing involvement, (4) high emotional involvement, ( 5) brand and image influence, and (6) financial involvement. The research results show that with low involvement products tend to focus more on efforts to increase brand awareness and provide information that is easily accessible to consumers. The strategies used include promotions via sosial media and giving discounts. In contrast, with high involvement products place more emphasis on developing a strong brand image and increasing consumer emotional involvement through a personalized purchasing experience and adequate after-sales service. In terms of purchasing and financial involvement, high involvement products require a more complex strategy and greater investment in marketing compared to low involvement products. This research provides insight for in Meulaboh to design effective marketing strategies according to the characteristics of their products, both low and high involvement.